Differential expression of the virulence gene nleB among Shiga toxin-producing Escherichia coli strains - Cadona, Jimena Soledad (2020)
Shiga toxin-producing Escherichia coli (STEC) is a zoonotic foodborne pathogen associated with hemolytic uremic syndrome (HUS) that vary in their ability to cause disease in humans. STEC represents a serious problem for public health and Argentina is the country with the highest HUS incidence worldwide. Non-LEE effector (nle) genes, present on pathogenicity islands (PAIs), encode translocated substrates of the type III secretion system (T3SS), which could have an important role in STEC virulence. Particularly, nleB is one of the main effector genes proposed as a virulence marker that is involved in the action of T3SS during the STEC infection. NleB inhibits the inflammatory response of the host cell allowing the bacteria to persist in the first stage of the infection. In order to identify the potential risk of STEC strains for public health, the aim of this study was to evaluate and compare basal nleB transcription of 24 STEC strains belonging to 10 serotypes isolated from cattle, food and patients. The results showed differences in nleB transcription among strains. Some non-O157:H7 strains presented transcription levels above the control, an O157:H7 HUS-producing strain. On the other hand, no significant differences were found in basal transcription levels associated with origin or serotype but differences were found between HUS and non-HUS strains. These differences in nleB transcription may be of importance in STEC pathogenesis and could help to differentiate high and low virulence STEC strains.